2009
DOI: 10.1002/jmv.21634
|View full text |Cite
|
Sign up to set email alerts
|

Serum KL‐6 levels as a biomarker of lung injury in respiratory syncytial virus bronchiolitis

Abstract: To evaluate whether KL-6 concentration is a useful biomarker of the severity of respiratory syncytial virus (RSV) bronchiolitis, we determined KL-6 concentrations in patients with RSV bronchiolitis with or without chronic heart disease (CHD). We enrolled 52 patients who had been diagnosed with RSV bronchiolitis and required admission to the hospital at the Department of Pediatrics of Fukushima Medical University School of Medicine from 2004 to 2005. These patients were divided into two groups: Group 1 consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…KL‐6 serum levels in ARDS may reflect the alveolar epithelial cell damage induced by mechanical ventilatory support 5 . High peripheral levels of this protein have also been reported in Legionella , Pneumocystis jivorecii infections, 6,7 and measles‐associated pneumonia, 8 as well as in viral pneumonia 9 …”
Section: Introductionmentioning
confidence: 92%
“…KL‐6 serum levels in ARDS may reflect the alveolar epithelial cell damage induced by mechanical ventilatory support 5 . High peripheral levels of this protein have also been reported in Legionella , Pneumocystis jivorecii infections, 6,7 and measles‐associated pneumonia, 8 as well as in viral pneumonia 9 …”
Section: Introductionmentioning
confidence: 92%
“…The mechanisms underlying RSV-induced lung disease and the associated long-term consequences remain incompletely understood, although lung inflammatory responses likely play a central role in promoting pathogenesis 16 17 . RSV infection can progress to ARDS, the most severe form of ALI that further contributes to morbidity 18 in infants 19 20 21 . Notably, our recent study showed that ACE2 is involved in influenza H7N9-induced lung injury and that use of a recombinant ACE2 protein alleviates the severity of ALI 15 .…”
mentioning
confidence: 99%
“…Primary Hypothesis 2, Nested Case-Control Study: Preliminary data from previous studies provide estimates of selected biomarkers, including leukotrienes, CC-16, KL-6, IL-18, TNF-α, and HNE. Estimates of minimal detectable differences (two sided α = 0.05) are given in Table 4, for different numbers of asthma cases identified [46][47][48][49][50].…”
Section: Power Calculationsmentioning
confidence: 99%